3 Conversation analytic study of communication with the relatives and friends of patients in a hospice: study protocol. Issue 3 (1st September 2017) - Anderson, Rebecca; Stone, Paddy; Low, Joe; Parry, Ruth; Tookman, Adrian; Lodge, Philip; Finlay, Dori-Anne; Wood, Barbara; Bloch, Steven
Abstract : Introduction: Family members of patients near the end-of-life value accurate prognostic information that is communicated sensitively by experienced healthcare professionals. This provides opportunities to say goodbye and make decisions about care. Current research is limited and has mostly focused on discussions early in the illness trajectory and with patients and not relatives. Aims and methods: This study aims to investigate communication about prognosis and end-of-life care between expert healthcare professionals and the relatives and friends of patients who lack capacity and are approaching the end-of-life. We will record conversations between experienced healthcare professionals and relatives of inpatients at a hospice. Recordings will be analysed using conversation analysis to identify practices used by healthcare professionals and relatives to attempt and accomplish communicative tasks. These tasks are likely to include: raising prognosis and care, receipt of information by relatives, communicating uncertainty, and ending these conversations. Healthcare professionals will participate in a focus group on what makes a 'good' conversation. Relatives will be invited to take part in one-to-one interviews 3–6 months later to gather their perspectives about experiences of communication about end-of-life care and prognosis. Results: We anticipate starting data collection in October 2017. Conclusion: No study to date has directly examined how healthcare professionals communicate prognostic information and discuss care with friends/relatives at the very end-of-life. Findings will therefore provide valuable new information and contribute to developing communication skills interventions for less experienced clinicians working in palliative care settings.